A potential role of cyclin-dependent kinase inhibitor 1 (p21/WAF1) in the pathogenesis of endometriosis: Directions for future research. (December 2019) - Zarkadoulas, Nikolaos; Pergialiotis, Vasilios; Dimitroulis, Dimitrios; Stefanidis, Konstantinos; Verikokos, Christos; Perrea, Despina N.; Kontzoglou, Konstantinos
Abstract: Endometriosis is a common gynecological disorder that affects approximately 6–10% of the female population impairing the quality of life of patients. Several pathophysiologic pathways have been proposed as potential regulators of its severity; however, to date, the processes that trigger the onset and that influence the severity of the disease are not fully understood; hence, leading to disease recurrence in approximately 10–67% of cases. Cyclin-dependent kinase inhibitor 1 (p21/WAF1) is a protein that is a major target of p53 and is related to cell cycle arrest (it regulates transition from the G1 to the S phase) when DNA damage is detected. Its activity has been also linked to the angiogenic potential of tumors as it promotes the expression of various kinases that are responsible for endothelial development and function. Although several articles have underlined the importance of this protein in cancer cell development and tumor growth, there are no relevant data in the field of endometriosis. Indirect evidence suggests, however, that it may be involved in the pathogenesis of endometriosis as it inhibits the activity of various kinases which have been correlated with the course and severity of the disease. The present article investigates the background theory that implies the potential role of cyclin-dependent kinase inhibitor 1 (p21/WAF1) in the pathogenesis of endometriosis. Implications for future research are also provided given that indirect evidence seem to associate downregulation of p21 with decreased growth and invasiveness of human endometrial stromal cells.